PERAN INDONESIAN DIASPORA NETWORK (IDN) DALAM PENYEBARAN KEBUDAYAAN INDONESIA DI MALAYSIA - Syaidina, Nazla Fatma; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Indonesian Diaspora Network (IDN) is a non-governmental organization engaged in the development of the diaspora around the world, including Malaysia. IDN is a non-governmental organization that helps disseminate through various activities, working with the Indonesian diaspora in Malaysia, the Indonesian Embassy and the Guidance Studio at the Indonesian School, Kuala Lumpur in making activities and festivals. The purpose of this paper is to describe the activities of IDN in spreading Indonesian culture in Malaysia.This research is a qualitative research method with a phenomenological research method and this phenomenological study describes the general understanding of a number of individuals on their various life experiences related to the concept/phenomenon. IDN chapter Malaysia in spreading culture is engaged in festivals, Indonesian dances, conferences, and UMKM exhibitions. Keywords: Indonesia, Malaysia, Indonesian Diaspora Network, Diaspora